Case Report on Pinna: An Unusual Site for Verrucous Carcinoma - Khan, Sidra; Akulwad, Shivkumar Balaji; Sonone, Jayant (Indian Journal of Medical and Paediatric Oncology, 2020)
Verrucous carcinoma is an uncommon variant of well-differentiated squamous cell carcinoma and is frequently seen in the oral cavity and larynx having some relation with tobacco chewing, whereas, its presentation over the ear is a rare entity. Here, we report the case of a 70-year-old female patient with complaints of cauliflower-like mass over her left pinna which was managed by doing an excisional biopsy and diagnosed as verrucous carcinoma on histopathology.
Keywords: Carcinoma; pinna; unusual site; verrucous